The Evolution of Bacterial Genome Architecture - Bobay, Louis-Marie; Ochman, Howard (Frontiers in Genetics, 2017)
The genome architecture of bacteria and eukaryotes evolves in opposite directions when subject to genetic drift, a difference that can be ascribed to the fact that bacteria exhibit a mutational bias that deletes superfluous sequences, whereas eukaryotes are biased toward large insertions. Expansion of eukaryotic genomes occurs through the addition of non-functional sequences, such as repetitive sequences and transposable elements, whereas variation in bacterial genome size is largely due to the acquisition and loss of functional accessory genes. These properties create the situation in which eukaryotes with very similar numbers of genes can have vastly different genome sizes, while in bacteria, gene number scales linearly with genome size. Some bacterial genomes, however, particularly those of species that undergo bottlenecks due to recent association with hosts, accumulate pseudogenes and mobile elements, conferring them a low gene content relative to their genome size. These non-functional sequences are gradually eroded and eliminated after long-term association with hosts, with the result that obligate symbionts have the smallest genomes of any cellular organism. The architecture of bacterial genomes is shaped by complex and diverse processes, but for most bacterial species, genome size is governed by a non-adaptive process, i.e., genetic drift coupled with a mutational bias towards deletions. Thus, bacteria with small effective population sizes typically have the smallest genomes. Some marine bacteria counter this near-universal trend: despite having immense population sizes, selection, not drift, acts to reduce genome size in response to metabolic constraints in their nutrient-limited environment.